Hydration practices and water intake among truck and tanker drivers in Ghana - Mustapha Amoadu; Susanna Aba Abraham; William Akoto-Buabeng; Jones Abekah Baah; Edward Wilson Ansah; Jessica Ayensu (Discover Public Health)
Abstract Background Proper hydration is essential for long-distance drivers to maintain health and cognitive function while on the road. However, many drivers face barriers to meeting the recommended daily water intake, potentially compromising their health and safety and that of other road users. This study aimed to assess hydration practices, barriers, and factors influencing water intake among truck and tanker drivers in Ghana. Methods A cross-sectional survey was conducted among 1575 truck and tanker drivers using a survey questionnaire. Data on water intake, beverages consumed, demographics factors, work conditions, and health status were collected. Chi-square and binary logistic regression analyses were used to identify predictors of meeting the recommended daily water intake of 3000 mL or more per day. Results The study found that only 14.2% (95% CI 12.5%, 15.9%) of the truck and tanker drivers met the recommended daily water intake (≥ 3000 mL), with 85.8% (95% CI 83.9–87.7%) consuming less water per day. Energy drinks, coffee, and bissap were the most commonly consumed beverages by the drivers while on the road. Key barriers included avoiding frequent urination and lack of rest stops. Only 4.8% (95% CI 3.7–6.1%) of drivers had high knowledge of dehydration symptoms. Multivariate analysis revealed that older age, tertiary education, longer driving experience, higher income, and having a co-driver increased the likelihood of meeting the recommended daily water intake. Conversely, regular shift work reduced the likelihood of adequate daily water intake. Conclusion Most truck and tanker drivers in this study did not meet the recommended daily water intake, which may increase the rate of dehydration and compromise drivers’ cognitive function while on the road. Interventions promoting regular hydration, especially for drivers working regular shifts, are needed to improve health outcomes and safety on the road.